1969
DOI: 10.1007/bf00148402
|View full text |Cite
|
Sign up to set email alerts
|

Solar activity and recurrences in magnetic-field distribution

Abstract: A study of the Mount Wilson magnetic-field synoptic chart material divided into latitude zones for the interval 1959-67, and a comparison of the data with sunspot groups have provided a better understanding of the structure of the background-field pattern and its relation to activity. The interaction of old and new fields within the pattern seems to result in long-lived sections of alternating polarity in both hemispheres. We postulate subsurface sources with rotation periods of about 27 days which produce act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
2

Year Published

1971
1971
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(39 citation statements)
references
References 8 publications
3
34
0
2
Order By: Relevance
“…This poleward drift of the weak, decayed magnetic flux appears in Figure 17 as plumes of one dominant polarity, the trailing sunspot polarity, at high latitudes between about 40 ∘ and 65 ∘ , sometimes referred to as a "rush to the poles". Such patterns were first reported by Bumba and Howard (1969) who named them unipolar magnetic regions. The dominant polarity of the poleward plumes is of opposite sign in each hemisphere, and it alternates from cycle to cycle.…”
Section: Chromospheric Synoptic Maps and Potential-field Extrapolationsmentioning
confidence: 73%
“…This poleward drift of the weak, decayed magnetic flux appears in Figure 17 as plumes of one dominant polarity, the trailing sunspot polarity, at high latitudes between about 40 ∘ and 65 ∘ , sometimes referred to as a "rush to the poles". Such patterns were first reported by Bumba and Howard (1969) who named them unipolar magnetic regions. The dominant polarity of the poleward plumes is of opposite sign in each hemisphere, and it alternates from cycle to cycle.…”
Section: Chromospheric Synoptic Maps and Potential-field Extrapolationsmentioning
confidence: 73%
“…ARs tend to emerge in the immediate vicinity or within the boundaries of an existing AR (Bumba and Howard, 1969). Liggett and Zirin (1985) and later Harvey and Zwaan (1993) showed that there is a 10 to 22-fold higher emergence rate within existing ARs than in the quiet sun.…”
Section: Clustering or Nesting Tendency Of Flux Emergencementioning
confidence: 97%
“…gions over one solar cycle, but not from one cycle to the next. Bumba and Howard [1969] demonstrated rigid rotation of low-latitude (+20 ø ) patterns in the solar magnetic field which persisted for several months. On a longer timescale, Bogart [1982] found a persistence of 27-day modulations of daily suns?ot numbers over a period of 128 years, consistent with long-lived active longitudes.…”
Section: Introductionmentioning
confidence: 99%